2019
DOI: 10.3389/fimmu.2019.01309
|View full text |Cite
|
Sign up to set email alerts
|

Gal-3 Deficiency Suppresses Novosphyngobium aromaticivorans Inflammasome Activation and IL-17 Driven Autoimmune Cholangitis in Mice

Abstract: Gal-3 has the role in multiple inflammatory pathways. Multiple-hit etiology of primary biliary cholangitis (PBC) and evolving immune response at various stages of the disease includes involvement of Gal-3 in PBC pathogenesis. In this study we aimed to clarify the role of Gal-3 in Novosphingobium aromaticivorans ( N. aromaticivorans ) induced biliary disease. Autoimmune cholangitis was induced in mice by two intra-peritoneal injections of N. aromaticivor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(42 citation statements)
references
References 45 publications
(63 reference statements)
1
41
0
Order By: Relevance
“…Previous studies have shown that Galectin-3, a lectin produced by macrophages, may activate the NLRP3 inflammasome in the liver and contribute to collagen deposition in a murine model of cholestasis [98]. Interestingly, treatment of mice with Davanat, a registered inhibitor of Galectin-3 that is currently being studied in clinical trials, determined a significant reduction in inflammasome activation and biliary damage in a model of autoimmune cholangitis [99]. Vardenafil, a phosphodiesterase-5 inhibitor, has been shown to significantly reduce the expression of Nlrp3 and inflammasome components in a cholestatic murine model induced by lithocolic acid administration [100].…”
Section: Inflammasome Activation In Cholestatic Liver Injurymentioning
confidence: 99%
“…Previous studies have shown that Galectin-3, a lectin produced by macrophages, may activate the NLRP3 inflammasome in the liver and contribute to collagen deposition in a murine model of cholestasis [98]. Interestingly, treatment of mice with Davanat, a registered inhibitor of Galectin-3 that is currently being studied in clinical trials, determined a significant reduction in inflammasome activation and biliary damage in a model of autoimmune cholangitis [99]. Vardenafil, a phosphodiesterase-5 inhibitor, has been shown to significantly reduce the expression of Nlrp3 and inflammasome components in a cholestatic murine model induced by lithocolic acid administration [100].…”
Section: Inflammasome Activation In Cholestatic Liver Injurymentioning
confidence: 99%
“…We used the model of PBC induced by Novosphingobium aromaticivorans infection of C57BL/6 mice to further explore the role of Gal-3 in PBC pathogenesis and its role in NLRP3 inflammasome activation. We found significantly higher percentage of NLRP3 expressing dendritic cells and macrophages, higher production of IL-1β and higher expression of NLRP3 and ASC in the livers of Gal-3 +/+ mice early after infection with N. aromaticivorans in comparison with the group of Gal-3 −/− mice [ 155 ].…”
Section: Galectin-3mentioning
confidence: 99%
“…The role of NLRP3 in driving Th-17 responses in the GI tract needs to be clarified since Tian et al reported that activation of NLRP3 promotes IL-17 production in autoimmune cholestasis generated by a dominant negative isoform of the TGFβ receptor II (TGFβRII) [21]. In line with this, Arsenijevic et al recently described a central role of NLRP3 in driving IL-17 in an infectious model of cholangitis as well [22]. In contrast, NLRP3-deficient mice induced with colitis released more IL-17 [9].…”
Section: Discussionmentioning
confidence: 96%